Influence of liquid organic manures on soil properties of garden pea (Pisum sativum L. var. hortense) - PHUKAN, RASHMI; BURAGOAHIN, NAYANMONI; NANDY, TANTUJA; GOGOI, KISHALAYEE; GOSWAMI, RATNA KINKOR (Journal of Soil and Water Conservation, 2026)
A field experiment was conducted to study the effect of different liquid organic manures on soil properties of garden pea at the Instructional cum Research Farm, Biswanath College of Agriculture, AAU, Biswanath Chariali in the rabi season during 2024-2025. The experiment was laid out in Randomized Block Design with seven treatments and three replications. The study revealed that there was significant difference among the treatments with respect to different soil parameters. The treatment T4 (Vermiwash @10%) increased soil pH (5.51), T5 (Jeevamrit @5%) markedly reduced bulk density (1.35 g cm-3), enhanced organic carbon (0.84%) and soil microbial population (25.29×10 6 cfu g-1 soil ) while RDF recorded the highest available N (424.48 kg ha-1), P2O5 (38.58 kg ha-1) and K2O (334.62 kg ha-1). These results indicate that although RDF ensures rapid nutrient availability, organic inputs such as Jeevamrit and Vermiwash significantly improve soil quality, emphasizing their potential for sustainable soil fertility management in organic production systems.